Fundación, esplendor y colapso de la iglesia de San Miguel de Piura (1534-1578), primer templo del Perú - Astuhuamán Gonzáles, César W. (Pontificia Universidad Católica del Perú. Fondo Editorial, 2016)
Esta investigación analiza la infraestructura e instituciones imperiales desarrolladas por los incas y españoles para controlar y administrar la región Piura mediante Piura La Vieja (o San Miguel de Piura). Dos preguntas son abordadas: ¿Cuáles fueron las funciones de las edificaciones institucionales? y ¿cómo sus funciones fueron cambiando desde los períodos prehispánico al Colonial Transicional? Para responderlas, combiné fuentes documentales y evidencias arqueológicas. Los españoles fundaron San Miguel en 1534 y, en 1539, una iglesia católica fue construida según fuentes documentales, la cual operó hasta 1578. Durante el trabajo de campo de 2005, 2008 y 2011, se excavó una edificación, construida sobre una prehispánica, localizada al sur de la plaza central, y se registraron componentes arquitectónicos de una iglesia: atrio, puerta principal, campanario o espadaña, muro perimétrico, altar y sacristía. La importancia de la iglesia radica en que es la única edificación sobreviviente de las siete iglesias tempranas construidas en el Perú antes de 1540. Este artículo es organizado en cinco partes: la primera está dedicada a explorar el período prehispánico (1800 a.C.-1532 d.C.); la segunda, al establecimiento hispano de San Miguel de Piura; la tercera y cuarta, al ascenso y colapso del sitio; finalmente, se presentan algunas conclusiones preliminares y futuras investigaciones son presentadas.

The aim of this research is to analyze the imperial infrastructure and institutions developed by the Inca and Spaniards to control and administer the Piura Region through the major center of Piura La Vieja (or San Miguel de Piura). This study leads with two main questions: What were the functions of the institutional buildings at Piura La Vieja, and how did these functions change from the pre-Hispanic to Transitional Colonial periods? To answer these questions, I developed a methodology to concede the limited documentary sources and surviving archaeological evidence. The Spaniards established San Miguel de Piura in 1534 and according to early documentary sources, a Catholic church was built circa 1539, which operated until 1578. During the 2005, 2008 and 2011, field seasons at Piura La Vieja we identified and excavated a structure to the south of the central plaza, oriented from North-West to South-East. The structure was identified and recorded as the architectural remains of a church, including an atrium, main entrance, tower, outer wall, altar, and sacristy. This church was built over a pre-existing pre-Hispanic building which followed a different axial orientation. The church of San Miguel de Piura is significant in that it is the only surviving building of the first seven churches built in Peru before 1540.This article is organized in five parts: the first is dedicated to explore the pre-Hispanic Period (1800 a.C.-1532 d.C.), the second to the Spanish establishment of San Miguel de Piura, the third to the brief rise of San Miguel, the fourth to the collapse of the site. Finally, some preliminary conclusions and directions for further research are presented.
Foundation, splendour, and collapse of the San Miguel de Piura church (1534- 1578), the first catholic church of Peru
Keywords: Período Colonial Transicional; Piura; Edificación Religiosa; Culto; Arquitectura; Transitional Colonial Period; Piura; Religious Building; Cult; Architecture; https://purl.org/pe-repo/ocde/ford#6.01.02